‘Youth-on-Youth’ constructivist approach in virtual classroom across two cultures : a case study of Malaysian and American University students - Au Yong Geok Lian (Universiti Kebangsaan Malaysia, 2011)
This article describes a semester-long, team-taught global videoconference class that took place between students enrolled at the University of Delaware in the United States of America and Universiti Tunku Abdul Rahman in Malaysia. The class, held in 2008 and again in 2009, used a “youth-on-youth” constructivist approach. Each group of students taught the other group about their young lives using videoconference technology, ‘Facebook’-style blogging, digital filmmaking,and instant messaging. This research project seeks to understand the relationship between technology use (especially among end users) and youths in the way they learn. How end-users (students) and technology, (videoconferencing and new communication technology) go hand-in-hand to construct a meaningful educational learning outcome in the virtual classroom context. The findings suggest more in-depth exploration and socio-cultural constructivist approach of employing technology in teaching and learning process. It challenges the superficial understanding of the linear relationship between technology, and teaching and learning in the modern classroom context, that there are other equally important social and cultural factors involved. And also from the cross-cultural experience, students gained fruitful learning experiences, as they create their own learning identity, reflect and question their own cultural values by seeing things through the eyes of ‘others’. Although students from both universities shared similarities in terms of popular culture, music, digital games and tools of new communication technology, local and national social-cultural differences still persist among students of the United States of America and Malaysia.